Building Brand Image Through Character Education in Kampung Sawah Elementary School - Nuriyati Samaatan; Marwan Londol; Kamaruddin Salim; NA Ramadhani (Siber Nusantara Research Publisher, 2026)
Character education not only serves as a pillar for students' moral development but also has the potential to become a competitive advantage that strengthens the image of an educational institution. This study aims to analyze the strategy of building a school's brand image through the implementation of character education at Kampung Sawah Elementary School. A descriptive qualitative approach was employed in this research. Data collection was conducted through observation, in-depth interviews with the principal, teachers, and parents, as well as through participant observation and documentation. The results indicated that the brand image was built by balancing brand identity and brand image, developing a brand identity system, aligning the brand with the product, humanizing the brand personality, and strengthening the brand as a symbol. Meanwhile, the character education established by SD Kampung Sawah provides character learning through routines such as praying before and after class, nurturing students through Quranic memorization, and fostering honesty, tolerance, discipline, hard work, creativity, and independence through outdoor learning processes. Cultivating democratic values and curiosity is achieved through various activities, such as outbounds and camping. National spirit and patriotism are implemented in a structured manner by the school to commemorate national holidays. Appreciating achievements, friendliness, communicativeness, and peace-loving behavior are implemented through collaborative work. A fondness for reading, environmental awareness, social care, and responsibility is integrated into both the classroom learning process and outdoor education involving the students. The Instagram social media account @salamkpsawah is utilized as one of the media channels to build the brand image of SD Kampung Sawah Depok.